1963
DOI: 10.1152/ajplegacy.1963.204.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture study of composition of proximal and distal tubular fluid in rat kidney

Abstract: Fluid was collected by micropuncture from proximal and distal convolutions of anesthetized rats and analyzed for inulin, sodium, urea, and total osmotically active solute. The proximal fluid/plasma (F/P) sodium ratio was not significantly different from unity in antidiuretic animals, but was as low as 0.78 during mannitol diuresis. The distal F/P sodium ratio averaged 0.62 in antidiuresis, and 0.24 during osmotic diuresis. The data are interpreted to indicate active sodium transport by both proximal and distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(61 citation statements)
references
References 1 publication
8
53
0
Order By: Relevance
“…These studies, however, gave no convincing evidence for large reductions in fractional fluid reabsorption in the proximal tubule, nor did they indicate the extent to which more distal sites might be involved. Moreover, both Windhager and Giebisch (8) and Ullrich, Schmidt-Nielsen, O'Dell, Pehling, Gottschalk, Lassiter, and Mylle (9) observed that early distal TP: F sodium ratios were, in fact lower during mannitol infusions; thus the actual load of sodium presented to the distal tubule might be little or no greater than in the control antidiuretic state.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies, however, gave no convincing evidence for large reductions in fractional fluid reabsorption in the proximal tubule, nor did they indicate the extent to which more distal sites might be involved. Moreover, both Windhager and Giebisch (8) and Ullrich, Schmidt-Nielsen, O'Dell, Pehling, Gottschalk, Lassiter, and Mylle (9) observed that early distal TP: F sodium ratios were, in fact lower during mannitol infusions; thus the actual load of sodium presented to the distal tubule might be little or no greater than in the control antidiuretic state.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been demonstrated in the rat, under freeflow conditions, that tubule fluid to plasma (TF: P) sodium concentration ratios during hypertonic mannitol infusions fall below unity and tend to approach the value of the limiting gradient at the end of the proximal tubule (8,9). These studies, however, gave no convincing evidence for large reductions in fractional fluid reabsorption in the proximal tubule, nor did they indicate the extent to which more distal sites might be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for suspecting that these cells were sensor cells was the fact that they are located very close to the end of the thick ascending limb (TAL). Before the "modern era" of macula densa research in the 1960s, work by Gottschalk and colleagues had found that the [NaCl] of the early distal tubule, that segment just beyond the macula densa, was very low, suggesting that there was salt transport without concomitant water abstraction in the TAL [13]. More importantly, the degree of dilution of tubular fluid was dependent upon the flow rate through this segment [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chasis & Smith, 1938), dog (e.g. Shannon, 1938) and rat (Ullrich, Schmidt-Nielsen, O'Dell, Pehling, Gottschalk, Lassiter & Mylle, 1963). Changes in potassium and ammonium outputs are more variable in magnitude and even in direction.…”
Section: Introductionmentioning
confidence: 99%